Developing Jurisprudential Inquiry Based Learning Model of Teaching Fiqh at Madrasah Tsanawiyah - Rahmiati Rahmiati; Muhammad Zubir; Muhiddinur Kamal; Muhamad Rezi; Muhammad Zainuddin bin Arriafdi (AT-TA'LIM, 2021)
Learning is the most significant activity in education. Through learning activities, the goals of education are achieved. Students’ success in learning mostly depends on their mastery to learn independently and on how they manage their study. The research aims to develop learning model at Madrasah Tsanawiyah, to make the learning process triggers students to be more creative and study better. The method used in the research refers to the nature of Research and Development. The steps of the study are preliminary study, development, and product test. The study found that the development of a jurisprudential inquiry-based learning model for learning Fiqh helps students to improve their learning outcomes. The model has significantly proven effective to support students’ behavior change, thus their achievement increases.